So many ways to naturally kill a cancer cell - Mitchison, Timothy J. (BMC Biol, 2021)
Natural killer (NK) cells participate in cancer immunosurveillance and cancer immunotherapy. Live cell imaging of cancer cells targeted by NK cells, published today in BMC Biology by Zhu et al., reveals a remarkable diversity of programmed cell death pathways induced in individual cells. Pathway choice depends on the state of the target cell actin cytoskeleton and a novel death pathway, granzyme-induced necroptosis, could be of broad importance in cancer immunotherapy.